Violence against pregnant women and associated factors in the city of Governador Valadares - Defilipo, Érica Cesário; Chagas, Paula Silva de Carvalho; Ribeiro, Luiz Cláudio (Revista de Saúde Pública, 2020)
OBJECTIVE: To characterize violence against women during pregnancy and to verify its association with socioeconomic, demographic, obstetric, behavioral factors, health care and diseases during pregnancy. METHODS: Cross-sectional study carried out with puerperal women whose birth took place at the Municipal Hospital of Governador Valadares, in Minas Gerais, from May 2017 to July 2018. Data collection was performed through interviews, and complementary information was obtained by analyzing the prenatal file and medical records. For data analysis, logistic regression was used. RESULTS: The total of 771 puerperal women participated in the study. Of these, 62 (8.0%) reported having suffered physical, psychological or sexual violence during pregnancy. The pregnant women most likely to have suffered violence were alcohol dependent (OR = 4.97; 95%CI 2.30–10.75; p < 0.001), those who did not perform prenatal care (OR = 3.88; 95%CI 1.00–15.09; p = 0.050), those who used health services in an emergency during pregnancy (OR = 2.47; 95%CI 1.42–4.30; p = 0.001) and who had gestational diabetes (OR = 2.59; 95%CI 1.06–6.32; p = 0.037) and sexually transmitted diseases (OR = 3.85; 95%CI 1.41–10.50; p = 0.009). CONCLUSION: Violence against pregnant women is associated with behavioral factors and related to health care and diseases during pregnancy. It is essential to recognize factors associated by health professionals through actions to track situations of violence against women since the beginning of prenatal care, in order to enable early intervention.OBJECTIVE: To characterize violence against women during pregnancy and to verify its association with socioeconomic, demographic, obstetric, behavioral factors, health care and diseases during pregnancy. METHODS: Cross-sectional study carried out with puerperal women whose birth took place at the Municipal Hospital of Governador Valadares, in Minas Gerais, from May 2017 to July 2018. Data collection was performed through interviews, and complementary information was obtained by analyzing the prenatal file and medical records. For data analysis, logistic regression was used. RESULTS: The total of 771 puerperal women participated in the study. Of these, 62 (8.0%) reported having suffered physical, psychological or sexual violence during pregnancy. The pregnant women most likely to have suffered violence were alcohol dependent (OR = 4.97; 95%CI 2.30–10.75; p < 0.001), those who did not perform prenatal care (OR = 3.88; 95%CI 1.00–15.09; p = 0.050), those who used health services in an emergency during pregnancy (OR = 2.47; 95%CI 1.42–4.30; p = 0.001) and who had gestational diabetes (OR = 2.59; 95%CI 1.06–6.32; p = 0.037) and sexually transmitted diseases (OR = 3.85; 95%CI 1.41–10.50; p = 0.009). CONCLUSION: Violence against pregnant women is associated with behavioral factors and related to health care and diseases during pregnancy. It is essential to recognize factors associated by health professionals through actions to track situations of violence against women since the beginning of prenatal care, in order to enable early intervention.